Potensi Pengembangan Pariwisata Halal Di Aceh - Supriyanti, Ayunda (Jurnal Sosiologi Pertanian dan Agribisnis, 2024)
Aceh Province is a province that has developed halal tourism for foreign Muslim tourists quite well compared to other regions. This can be seen from the application of a sharia-based system which has become part of the daily lifestyle of the people. The author's way of obtaining data is by reading relevant sources from documents, books, articles, magazines, news, and so on. An important effort to be made in the development of halal tourism in Aceh is the alignment of the budget towards the tourism industry. Tourism will not be successful if it is fully left to the independence of the community or letting the private sector work alone. Budget alignments are needed for the tourism industry by allocating realistic funds both for the development of infrastructure, main and supporting facilities and increasing the capacity of human resources in the field of tourism, especially halal tourism.